Equivalence of the Production and Consumption Methods of Calcuting the Value-Added Tax Base Application in Zambia - Pellechio, Anthony J. (International Monetary Fund, 1996)
Two methods of calculating the value-added tax (VAT) base, using production and consumption data, respectively, have been applied in different countries to estimate VAT revenue. It is not apparent that these methods should produce the same result for a particular country because each method requires different adjustments for exemptions. This paper establishes analytically the equivalence of the two methods. Both methods are applied to Zambia. Given the limitations of data, the two methods produce different results, yielding an estimated range for VAT revenue of 2-3 percent of GDP in 1995. Actual VAT revenue collected fell within this range